2015
DOI: 10.1371/journal.pone.0116466
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Phylogenetic Analysis of the Mitochondrial Genome of Shiraia bambusicola Reveals Special Features in the Order of Pleosporales

Abstract: Shiraia bambusicola P. Henn. is a pathogenic fungus of bamboo, and its fruiting bodies are regarded as folk medicine. We determined and analyzed its complete mitochondrial DNA sequence (circular DNA molecule of 39,030 bp, G + C content of 25.19%). It contains the typical genes encoding proteins involved in electron transport and coupled oxidative phosphorylation (nad1-6 and nad4L, cob and cox1-3), one ATP synthase subunit (atp6), 4 hypothetical proteins, and two genes for large and small rRNAs (rnl and rns). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 60 publications
5
39
0
1
Order By: Relevance
“…In order to determine the classification of S. bambusicola, nine fungal species were used for phylogenetic construction using the complete genome sequencing data downloaded from the NCBI database. The results from the phylogenetic analysis were basically consistent with previous studies (Liu et al, 2013;Shen et al, 2015), which showed that S. bambusicola is located in the order Pleosporales. The inferred phylogeny indicated that Stagonospora sp.…”
Section: Discussionsupporting
confidence: 91%
“…In order to determine the classification of S. bambusicola, nine fungal species were used for phylogenetic construction using the complete genome sequencing data downloaded from the NCBI database. The results from the phylogenetic analysis were basically consistent with previous studies (Liu et al, 2013;Shen et al, 2015), which showed that S. bambusicola is located in the order Pleosporales. The inferred phylogeny indicated that Stagonospora sp.…”
Section: Discussionsupporting
confidence: 91%
“…Given that the mitochondrial (mt) genome evolves more rapidly than the nuclear genome and has been shown to produce reliable phylogenetic trees, it has been established as an effective evolutionary marker in fungi (Wu et al 2009, Duò et al 2012, Youssar et al 2013, Shen et al 2015. Fungal mt genomes are frequently circular molecules consisting of 14 highly conserved protein coding genes related to oxidative phosphorylation (OXPHOS), one large (rrnL) and one small (rrnS) ribosomal RNA (rRNA) gene, and a set of transfer RNA (tRNA or trn) genes which can vary between species (Gray et al 1999, Lavín et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Two incomplete copies of atp6 were found on different strands of the mitogenomic DNA of Shiraia bambusicola, a Pleosporales member used as outgroup in this study (Shen et al, 2015). Three hypotheses can be drawn regarding mitochondrial gene duplications: First, copies could be undergoing subfunctionalization (Conant and Wolfe, 2008) where recombination events of fission and fusion are the drivers of such a process (Burger, Gray and Lang, 2003), however we did not see two functional copies of any ETC genes in any genome.…”
Section: Discussionmentioning
confidence: 65%
“…One hundred bootstrapped trees were generated and used to assign bootstrap support values to the consensus trees. The species Didymella pinodes (Okorski et al, 2016), Pseudovirgaria hyperparasítica (Braun et al, 2011), Phaeosphaeria nodorum (Hane et al, 2007) and Shiraia bambusicola (Shen et al, 2015) were used as outgroup.…”
Section: Phylogenetic Analysis and Divergence Times Estimatesmentioning
confidence: 99%